Suicide risk model based on the interpersonal theory of suicide: evidence in three regions of Mexico - Solis-Espinoza, Modesto (2023)
Background: Reports of suicidal behavior have increased in Mexico for years. In order to develop a more adequate suicide prevention strategy, it is necessary to understand its predictive factors, so the purpose of this research was to propose a model of suicidal risk in young people, taking into account one of the most current theories on the subject, Joiner's interpersonal theory. Method: A non-probabilistic sample of young people with suicidal ideation from three regions of Mexico was obtained by online survey (N=411), with mean age of 17.89 years (SD. 1.2), 336 women (81.8%), and 75 men (18.2%). Results: First, a multiple linear regression model was created to predict suicidal risk based on thwarted belongingness and perceived burden with 17% explained variance; then a second model was generated with the same variables and including other factors associated with suicide such as self-injury desires, impulsivity and suicide attempts, in addition to variables associated with family conflicts, improving the explained variance to 34%. Lastly, two properly adjusted structural equation models were obtained, one focused on suicidal risk (R2=.21; RMSEA=.026; CFI=.99) and the other on ideation (R2=.18; RMSEA=.070; CFI=.98). Conclusions: The main factors that explain suicidal risk are depressive symptoms, perceived burden and desires for self-injury. Further research on the effect of painful experiences as factors that could predict suicide attempt is suggested.